Home-made and commercial eco-enzymes alter plankton communities and water chemistry in Rawa Pening Lake, Central Java, Indonesia - SUSANTI PUDJI HASTUTI; SUCAHYO SUCAHYO; DESTI CHRISTIAN CAHYANINGRUM; RULLY ADI NUGROHO (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Hastuti SP, Sucahyo, Cahyaningrum DC, Nugroho RA. 2025. Home-made and commercial eco-enzymes alter plankton communities and water chemistry in Rawa Pening Lake, Central Java, Indonesia. Biodiversitas 26: 3843-3854. Eco-enzymes are increasingly used to improve water quality by reducing organic pollutants and balancing nutrient levels in rivers and other aquatic systems. However, their typically low pH and high concentrations of organic matter may increase Biological Oxygen Demand (BOD) and acidify the water, potentially altering freshwater plankton species composition and increasing the risk of eutrophication in aquatic ecosystems. This study aimed to assess the effects of commercial and home-made eco-enzyme on freshwater plankton community structure and water quality parameters using a controlled aquaria design with four concentrations (2.5-20% v/v). Controls without eco-enzymes were included for comparison. Key parameters including nutrient levels, BOD, Total Dissolved Solids (TDS), pH, plankton diversity and abundance were monitored throughout the study. Plankton diversity across different eco-enzyme types and concentrations was compared by generating diversity profiles using Renyi’s entropy values. Results showed that both types of eco-enzymes significantly altered water chemistry. BOD declined rapidly at 5% commercial and 2.5% (v/v) home-made eco-enzyme, while pH increased from 7.4 to 8.6 over time. Ammonia, nitrite, nitrate, and TDS levels rose with both eco-enzyme concentration and duration. At higher concentrations, commercial eco-enzymes promoted the dominance of Bacillariophyta and Cyanophyta, while home-made eco-enzymes favored Bacillariophyta and Chlorophyta. Although eco-enzymes stimulated microbial activity and organic matter decomposition, they also supported the growth of pollution-tolerant plankton species, potentially reducing overall biodiversity. Renyi entropy profiles revealed decreased richness and evenness, especially at higher concentrations. These results highlight that while eco-enzymes can contribute to water quality improvement, their ecological impacts, particularly on plankton communities, must be carefully considered. Further research is necessary to ensure their sustainable and responsible use in aquatic ecosystems.